The role of culture in the formation of personality A theoretical study of the contributions of the pioneers of the school of culture and personality - Hamza, PhD Ali Kadhem (Thi Qar Arts Journal, 2022)
As a result of the flourishing of ethnographic and ethnological studies at the end of the ninth century and in the twentieth century, anthropologists obtained abundant material that allows conducting comparative studies of different cultures and observing the vast differences between the main forms of personality in those cultures, which led to confirming the inadequacy of biological and genetic factors in explaining those differences. Determining the impact of environmental factors. Things that anthropological researchers sought to know from the personality research were many. They are concerned, for example, with the complexities of socialization as a process of cultural normalization, and this normalization aims mainly in all societies to inculcate the values, standards and beliefs of the traditional culture system in society in the mind of And the same individuals in the early childhood years, and because of the different culture systems, the basic personality models differ, and as Ralph Linton says, “The greatest technical achievement achieved by this research was done with the help of psychological studies, as it was intended to discover the personality type that represents the studied culture best representation considering that this Culture has molded each individual member of the group with its own molds and given him what he calls American anthropologists (cultural stereotyping) or (personal stereotyping)